Exsolution enhancement of metal-support co oxidation perovskite catalyst with parameter modification - G. L., Lew; N., Ibrahim; S., Abdullah; W. R., Wan Daud; W. K. W., Ramli (IOP Publishing Ltd, 2021)
This study aimed to further tune the capability of active metal exsolution onto the surface of the CO oxidative perovskite catalyst La0.7Ce0.1Co0.3Ni0.1Ti0.6O3 by tuning the reducing parameter. Under same calcination temperature of 800℃, XRD analysis shown that the precursors with calcination duration of 6 hours (S2T8H6) was able to achieve similar crystalline structure to those with calcination duration of 12 hours (S2T8H12). In order for the active metal (CoNi) to be exsolved onto the perovskite surface, reducing parameter such as temperature and duration are deemed crucial to the reduction process. The exsolution of the active metals was observed when the samples were treated under reducing condition with varying temperatures of 550℃ and 700℃ and duration from 200 to 300 minutes. Through comparison with their EDX readings, S2T8H6 treated under 700℃ and 300 minutes (S2T8H6-R7H5) achieved the highest weight percentage of surface Cobalt and Nickel of 3.83 and 2.81. It was clear that by tuning the temperature and duration of reduction, the exsolution of the active metals onto the surface of the perovskite could be improved resulting in better exposure and dispersion of active metals onto the surface of catalyst.